2016
DOI: 10.1186/s13256-016-0820-z
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure pulmonary edema - a life-threatening condition in an eye care setting: a case report

Abstract: BackgroundNegative pressure pulmonary edema is a potentially life-threatening complication after general anesthesia in young healthy individuals that results from upper airway obstruction followed by strong inspiratory effort. It is a known complication after nasal or upper airway surgery. Occurrence of such a life-threatening complication in an eye care setting where advanced intensive care is usually lacking is rare.Case presentationA 15-year-old Asian boy presented to our hospital with a penetrating eye inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Other procedure that increases the risk of NPPE includes oropharyngeal, head, and neck surgery. Five [812] of the reported 29 cases involved upper respiratory tract surgery, and 10 [1,3,6,7,1318] of the cases involved head and neck surgery, which may be related to tissue swelling and the sensitive dilator muscle of the upper airway in head and neck surgeries. Although our patient underwent endoscopic thyroidectomy with no wound in the neck skin, it was inevitable for neck tissue and muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Other procedure that increases the risk of NPPE includes oropharyngeal, head, and neck surgery. Five [812] of the reported 29 cases involved upper respiratory tract surgery, and 10 [1,3,6,7,1318] of the cases involved head and neck surgery, which may be related to tissue swelling and the sensitive dilator muscle of the upper airway in head and neck surgeries. Although our patient underwent endoscopic thyroidectomy with no wound in the neck skin, it was inevitable for neck tissue and muscle injury.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literatures reported that laryngospasm associated with intubation and general anesthesia was the most common cause of upper airway obstruction leading to NPPE in adult patients [ 1 ]. NPPE caused by airway obstruction often could be life-threatening disease [ 2 , 5 ]. If physician do not recognize that SAS could cause NPPE during sleep, a patient with SAS might miss an opportunity to take an adequate treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as a form of noncardiogenic pulmonary edema (NCPE) that results from the generation of high negative intrathoracic pressure following forced spontaneous breathing against upper airway obstruction after nasal or upper airway surgery. 1 It is reported that NPPE is seen in 0.1% of cases with general anesthesia requiring tracheal intubation, with postanesthetic laryngospasm is reported to be the reason in more than half of the cases. 2 Other causes of NPPE include foreign body aspiration, hematoma, smoking, obesity, delayed recovery from general anesthesia, obstructive sleep apnea syndrome, and oral and maxillofacial surgeries.…”
Section: Referencesmentioning
confidence: 99%
“…Negative pressure pulmonary edema (NPPE) is a sudden onset and life-threatening complication following general anesthesia in young healthy adults. It is defined as a form of noncardiogenic pulmonary edema (NCPE) that results from the generation of high negative intrathoracic pressure following forced spontaneous breathing against upper airway obstruction after nasal or upper airway surgery 1 . It is reported that NPPE is seen in 0.1% of cases with general anesthesia requiring tracheal intubation, with postanesthetic laryngospasm is reported to be the reason in more than half of the cases 2 .…”
mentioning
confidence: 99%